SOCIAL ECONOMIC ANALYSIS OF ILLEGAL FISHING FISHERS IN SPERMONDE ISLAND - Adri Arief (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2022)
The sustainable use of fish resources is closely related to fishing practices by fishermen. It is a classic problem that utilizing marine and fishery resources, the exploitation method carried out by fishermen often does not consider environmental sustainability aspects or is contrary to the principles of responsible fisheries management (Code of Conduct for Responsible Fisheries - CCRF). This study aims to examine IUU fishing activities from the socio-economic dimension, which under certain conditions will produce its own understanding, especially when it comes to traditional rights, resource share allocation, and the level of dependence on fishery resources. The type of research is qualitative research with a case study method. Data collection techniques are observation, interviews, and literature study. The data collected includes primary data and secondary data. The data analysis technique used is the content analysis method through the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that illegal fishing that occurs in the Spermonde Islands is dominant due to the pressure to fulfill economic needs, other factors are the low understanding of the importance of sustainable use of fishery resources; increasing demand for foreign markets, especially live fish; and inconsistency and weak law enforcement in preventing the use of explosives and drugs. Empirical data on resource potential is required and integrated into policy formulation in the form of responsible fisheries, including other activities that can be done by fishermen as alternative livelihoods, and ecosystem approaches for conservation and management of fish stocks of related species.